Skeletons in the closet? Using a bibliometric lens to visualise phytochemical and pharmacological activities linked to Sceletium, a mood enhancer - Reddy, Kaylan; Stafford, Gary I.; Makunga, Nokwanda P. (Frontiers in Plant Science, 2024)
Plants from the Sceletium genus (Aizoaceae) have been traditionally used for millennia by the Khoe and Khoen people in southern Africa, as an appetite suppressant as well as a mood elevator. In more recent times, this mood-elevating activity has been commercialised in the South African natural products industry for the treatment of anxiety and depression, with several products available both locally and abroad. Research on this species has seen rapid growth with advancements in analytical and pharmacological tools, in an effort to understand the composition and biological activity. The Web of Science (WoS) database was searched for articles related to ‘Sceletium’ and ‘Mesembrine’. These data were additionally analysed by bibliometric software (VOSviewer) to generate term maps and author associations. The thematic areas with the most citations were South African Traditional Medicine for mental health (110) and anxiolytic agents (75). Pioneer studies in the genus focused on chemical structural isolation, purification, and characterisation and techniques such as thin layer chromatography, liquid chromatography (HPLC, UPLC, and more recently, LC-MS), gas chromatography mass spectrometry (GC-MS), and nuclear magnetic resonance (NMR) to study mesembrine alkaloids. Different laboratories have used a diverse range of extraction and preanalytical methods that became routinely favoured in the analysis of the main metabolites (mesembrine, mesembranol, mesembranone, and Sceletium A4) in their respective experimental settings. In contrast with previous reviews, this paper identified gaps in the research field, being a lack of toxicology assays, a deficit of clinical assessments, too few bioavailability studies, and little to no investigation into the minor alkaloid groups found in Sceletium. Future studies are likely to see innovations in analytical techniques like leaf spray mass spectrometry and direct analysis in real-time ionisation coupled with high-resolution time-of-flight mass spectrometry (DART-HR-TOF-MS) for rapid alkaloid identification and quality control purposes. While S. tortuosum has been the primary focus, studying other Sceletium species may aid in establishing chemotaxonomic relationships and addressing challenges with species misidentification. This research can benefit the nutraceutical industry and conservation efforts for the entire genus. At present, little to no pharmacological information is available in terms of the molecular physiological effects of mesembrine alkaloids in medical clinical settings. Research in these fields is expected to increase due to the growing interest in S. tortuosum as a herbal supplement and the potential development of mesembrine alkaloids into pharmaceutical drugs.